Pengaruh Pelatihan Dan Motivasi Terhadap Kinerja Karyawan Pada PT Patra Trading - Silvianita, Anita; Ningrum, Siska Ayu (eProceedings of Management, 2024)
The decline in demand for raw materials was a result of the growth of the manufacturing industry in April. Thishas an impact on PT Patra Trading's sales performance. To address this, PT Patra Trading believes that propertraining can improve operational efficiency and ensure that employees can perform optimally in challengingsituations. This study aims to learn more about the influence of training and motivation variables on performanceat PT Patra Trading because organizations can succeed one of them because of properly managed humanresources, which include, training, motivation, and cooperation. This study will involve all employees of PT PatraTrading, so the population of this study is all employees of PT Patra Trading. The tang method used is quantitativeand the type of research is explanatory causality because it explains the influence of training (X1) and motivation(X2) on employee performance (Y). In collecting data, primary data types and secondary data are used. showingthat training, motivation and employee performance obtained using descriptive statistics are categorized as goodand show the significance of the influence between training and motivation has a significant influence partiallyand simultaneously on employee performance at PT Patra Trading.Keywords-training, motivation and employee performance.